Analisis Efektivitas Pemeriksaan Pajak Di Masa Pandemi Covid 19 Dalam Rangka Meningkatkan Target Penerimaan Pajak Studi Kasus Pada KPP Pratama Jakarta Pasar Rebo - Elisa Andriani a; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2021)
Taxes are obligations that must be paid by the public, both individuals and entities, from their income or income for the government. During the Covid-19 pandemic, mobility is disrupted and has an impact on tax audits. This study aims to analyze the effectiveness of tax audits during the Covid-19 pandemic in order to increase the target of tax revenue, a case  study  at  KPP  Pratama  Jakarta  Pasar  Rebo.  Data  collection techniques  in  this  study  were  conducted  by  means  of  interviews, observation and documentation. Technical data analysis in this study was  carried  out  by  means  of  qualitative  descriptive  research.  The results  of  this  study indicate that  inspections  during  the COVID-19 pandemic are considered ineffective because there are inhibiting factors that occur during tax audits such as PCR or swab tests before entering the  company,  incomplete  tax  documents,  termination  of  finance/tax employees due to income. decreased during the COVID-19 pandemic. During the COVID-19 pandemic, the efforts made by the KPP  Pratama Jakarta Pasar Rebo were very optimal, inspections were carried out online such as zoom meetings. Inspection documents can also be sent via email or through the post office etc.